Synthesis and structural chemistry of bis(pyridylimino)isoindolato-ruthenium complexes and their activity as mediators in the atom transfer radical polymerization (ATRP) of styrene - Camerano, José A.; Rodrigues, Anne-Sophie; Rominger, Frank; Wadepohl, Hubert; Gade, Lutz H. (Journal of organometallic chemistry, 2011)
The reaction of the Bispyridyl Isoindole (BPI) type ligands L1 and L2 (L1 = 1,3-Bis(2-(4-tert-butylpyridyl)imino) isoindole, L2 = 1,3-Bis(2-(5-bromo)imino)-5,6-dimethylisoindole) with [Ru(μ-Cl)2(cod)]x in presence of triethylamine using coordinating solvents like acetonitrile, dimethyl sulfoxide or pyridine cleanly gave the complexes [{BPI(L1,L2)}RuII(Cl)(S)2] (L1: S = acetonitrile (1), dimethyl sulfoxide (2), pyridine (3); L2: S = acetonitrile (4), dimethyl sulfoxide (5), pyridine (6)). In these complexes the BPI ligands meridionally coordinated to the ruthenium center as established by X-ray diffraction for complexes 3 and 6. The catalytic activity in the direct ATRP (Atom Transfer Radical Polymerization) of styrene was tested for complexes 1-6.